A Damage Constitutive Model for a Rock under Compression after Freeze-Thaw Cycles Based on the Micromechanics. (23rd July 2021) - Liu, Hongyan; Zhang, Xiaochen; Yan, Xidong
Abstract : The freeze-thaw cycles will cause continuous damage to the rock, which is much related to the microcrack length, rock permeability, and frost heaving pressure. However, the failure mechanism of the rock under compression after freeze-thaw cycles is not very clear; therefore, it is studied with the damage theory here. First of all, according to the hydraulic pressure theory, the relationship between the frost heaving pressure and the microcrack propagation length in one single microcrack is established based on the elastoplastic mechanics and fracture theory. Second, by assuming the total strain of the rock under compression is comprised of the initial damage strain, elastic strain, additional damage strain, and plastic damage strain, a constitutive model for a rock based on the deformation and propagation of the microcrack under compression after freeze-thaw cycles is established. Finally, the proposed model is verified with the test result. In all, the proposed model can perfectly reflect the deterioration of the rock mechanical behavior under compression after the freeze-thaw cycles.